Empirical Issues and Challenges for Multilevel Governance: The Case of the 2010 Vancouver Olympic Winter Games - Parent, Milena; Rouillard, Christian; Chappelet, Jean-Loup (Revue Gouvernance / Governance Review, 2018)
How did a large network of over 600 actors successfully organize itself to serve a mega project dominated by three levels of government, even as control rested with a non-profit entity, included other sectors, and the governments involved did not normally work well together? The purpose of this paper is to examine how the three levels of government in Canada established a network to coordinate efforts for hosting the 2010 Vancouver Olympic Winter Games. This case study was built by means of documents and interviews, and supported by participant observations. The network was not found to be dense, but did include a multiplexity of ties (e.g., transactions, communications, collaborations, and coordinating bridges) by actors serving diverse strategic goals and scopes of work. The case was compared to data collected for the 2012 London Olympic Games to draw out key network governance coordination themes. Nine governance themes emerged associated with governance structure, processes, and evaluation: coordination mechanisms; internal engagement, momentum, and motivation; external transparency; formalization; balancing autonomy and interdependence; co-location; readiness exercises; political alignment; and time. The findings provide a framework for examining the governance of multi-level, multi-sectorial networks created to undertake a mega project and indicate how a network’s public and non-profit organizations’ activities and procedures can be influenced, modified, and impacted by the other actors (i.e., other public or non-profit organizations).